Indigenous Peoples and Human Rights. - Thornberry, Patrick (Melland Schill studies in international law., 2005)
This study of the rights of indigenous peoples looks at the historical, cultural, and legal background to the position of indigenous peoples in different cultures, including America, Africa and Australia. It defines "indigenous peoples" and looks at their position in international law.